Rekonstruksi Kerangka Regulasi Penyelenggaraan Daycare untuk Memperkuat Perlindungan Anak dari Kekerasan: Restructuring the Regulatory Framework for Daycare Operations to Strengthen the Protection of Children from Violence - Setyowati, Dewi; Maharani, Putri Tiara (Perspektif Hukum, 2026)
Daycare operations encompass various aspects that are essential for ensuring the quality of service, comfort, and safety of children. The following are some key points typically covered in daycare operations: Facilities and Environment, Health and Hygiene, Caregivers, Educational Programs and Activities, Safety, Communication with Parents, Inclusion and Diversity, Licensing and Legal Compliance. However, current regulations governing daycare operations remain inadequate, and there is a high potential for violations of operating permits, as well as widespread incidents of violence against children in care. To maximize the role of daycare in supporting children’s development and assisting families, this study discusses the importance of strengthening regulations and policies related to daycare operations to ensure that the services provided meet standards of quality, safety, and child welfare. This study employs a normative research method that refers to legal norms found in laws and regulations related to daycare operations. The research approaches used are the legal-regulatory approach and the conceptual approach. This study is expected to make a theoretical contribution to the development of knowledge in the field of law and, in particular, to provide practical insights to the government as a basis for considering regulations and policies regarding the operation of daycare centers.